POETICS OF V. STEFANYK - Moskovkina, I. I. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
Article is devoted to on the poetics novelistic V. Stefanyka, determination of creative thinking in the context of Ukrainian writer of prose and the late nineteenth and early twentieth century, in particular typology еxpressionism.